Analysis of the spatial distribution of air pollutants in center of the city of Tabriz (District 8) and its relation with man-made environment - Aida Maleki; Parisa Ghobadi; Davoud Kahforoushan; Mohammad Hassan Sarbazan; Hamid Mansouri (توسعه پایدار شهری)
Air pollution is one of the problems of the present century all over the world. The aim of this study was to identify the major pollutants in Tabriz, District 8, and analyze their spatial distribution and investigate its relation with some components of man-made environment. To study the distribution of pollutants in the research area, information about the concentration of pollutants was measured by mobile equipment at 11 predetermined points between 10:00- 20:00 in different times and different days in June 2021 and with GIS software and distribution maps were extracted. The generated maps showed that the concentration of pollutants is directly related to the density of commercial land use and consequently the increase in traffic volume. To find the relationship between pollution concentration and urban typology, information about urban design components was extracted by using GIS software and the correlation coefficient between the concentrations of pollutants and the mentioned components was investigated. The results also showed a significant relationship between the concentration of suspended particles and the visibility factor to the sky as well as the density of building mass in the region. The concentration of carbon monoxide with the ratio of green space at the measuring points was inversely related and the pollutants NO2, SO2 and CO showed a significant relationship with the ratio of surface to unstructured and in fact building density. In addition, the relationship between the concentrations of pollutants with each other was also examined, indicating a strong direct relationship between the concentration of suspended particles (PM10 and PM2.5) together and the concentration of NO2, SO2 and CO with each other. In general, it can be concluded that the typology of the city plays a significant role in intensifying or adjusting the concentration of some air pollutants, and in critical areas, the air quality of the area can be improved to some extent by controlling urban design variables.